Preparation method of copper-zinc-tin-sulfur thin film and application of copper-zinc-tin-sulfur thin film in thin-film solar cell

By using ethylene glycol methyl ether as a solvent system and optimizing inkjet printing parameters, the problem of poor performance and ink stability in the existing technologies, and the preparation of high -efficiency CZTSSE film solar cell preparation.

CN119384060APending Publication Date: 2025-01-28SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411292151.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

In the prior art, the battery performance of CZTSSe solar cells produced by inkjet printing is poor, and the traditional solution ink system has stability problems, resulting in precipitation after long-term placement, affecting industrial production.

Method used

The use of ethylene glycol methyl ether (MOE) is used as a solvent to prepare a stable ink system. By optimizing inkjet printing parameters, including printing resolution and thermal treatment conditions, high -quality CZTS and CZTSSE film are prepared.

Benefits of technology

The long -term chemical stability of the front -drive body ink solution was achieved, the problem of precipitation was avoided, the material utilization rate was improved, and the high -efficiency CZTSSE film solar cell was obtained, which improved the photoelectric conversion efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384060A_ABST
    Figure CN119384060A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a copper-zinc-tin-sulfur thin film and application of the copper-zinc-tin-sulfur thin film in a thin-film solar cell. Firstly, the preparation method of the copper-zinc-tin-sulfur film is provided, ethylene glycol monomethyl ether is used as a solvent to prepare an air-stable ink system, the chemical stability of the obtained precursor ink aqueous solution is greatly improved, the precursor ink aqueous solution is still clear and transparent after being placed for a long time, precipitates are not prone to being generated, and a printer nozzle is prevented from being blocked; the long-term stability of a precursor solution multi-element complexing system is realized; the method is suitable for long-period industrial production; meanwhile, the high-quality CZTSSe thin film and the thin-film solar cell thereof are prepared by ink-jet printing based on the printing resolution of (250-300) * (250-300) dpi. The CZTSSe thin film is prepared by adopting an ink-jet printing technology, the technology has the advantages of low loss and low cost, and meanwhile, a high-performance and high-efficiency thin film solar cell can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy materials and devices, and more specifically, relates to a method for preparing a copper-zinc-tin-sulfur thin film and an application thereof in a thin-film solar cell. Background Art

[0002] Solar energy is widely regarded as a clean, renewable energy source that holds great promise in addressing society's growing energy needs. As a result, significant advances have been made in the field of solar cells over the past few decades.

[0003] At present, traditional thin-film solar cells, such as copper indium gallium selenide (Cu(In,Ga)Se 2 ), cadmium telluride (CdTe), and gallium arsenide (GaAs) have achieved commercially viable efficiencies. However, their shortcomings, such as the toxicity of Cd and As and the scarcity of In and Ga, have hindered the large-scale industrialization of photovoltaics. 2 ZnSn(S,Se) 4 , CZTSSe) solar cells have attracted extensive attention due to their excellent properties, such as suitable band gap (adjustable between 1.0 and 1.5 eV), non-toxicity, earth-abundant storage of constituent elements and high light absorption coefficient. Due to its numerous excellent properties, people have been committed to improving the energy conversion efficiency of CZTSSe solar cells.

[0004] The current method for preparing CZTSSe light-absorbing films is mainly spin coating. However, a large amount of ink splashes during the spin coating process, and only 2-5% of the precursor ink is effectively utilized, resulting in a high waste of materials. These limitations hinder the future low-cost large-scale production of CZTSSe solar cells. Compared with the spin coating method, inkjet printing technology is a simple and cost-effective technology that can effectively reduce production costs by improving the utilization rate of raw materials, which is conducive to large-scale industrialization. However, the cell performance of CZTSSe solar cells prepared by inkjet printing technology is still poor. For example, the light conversion efficiency of the CZTSSe solar cell prepared by the precursor ink prepared based on a mixed solvent (DMSO and DMF) prepared by the prior art combined with inkjet printing technology is only 10.1%, which is the highest efficiency of CZTSSe solar cells currently prepared based on inkjet printing technology (Ge Sijie.Cu 2 ZnSn(S,Se) 4Control of printable inks and research on performance of photovoltaic devices [D]. Sun Yat-sen University, 2022). At the same time, there are problems with inkjet printing inks with DMSO as the solvent system: the prepared precursor solution is a multi-component complex system. Since DMSO has a certain oxidizing property, the redox reaction in it will cause the stability of the precursor solution to decrease. The phenomenon is that the ink solution will produce precipitation after two days of storage. This is very unfavorable for long-term industrial production processes, and it is also easy to clog the nozzle; at the same time, as the light absorption layer of solar cells, the quality of CZTSSe thin films is the key to improving the performance of photovoltaic devices. The quality of thin films obtained by using DMSO-based inks using inkjet printing technology is low, and high-efficiency solar cell devices cannot be obtained. Therefore, it is urgent to optimize the current method of preparing CZTSSe solar cells based on inkjet printing technology to obtain higher-performance CZTSSe solar cells that can be applied to long-term industrial production. Summary of the invention

[0005] The purpose of the present invention is to overcome the above defects and shortcomings in the prior art and provide a method for preparing a copper-zinc-tin-sulfur thin film.

[0006] The second object of the present invention is to provide a copper-zinc-tin-sulfur thin film prepared by the preparation method.

[0007] The third object of the present invention is to provide application of the copper-zinc-tin-sulfur thin film in thin-film solar cells.

[0008] The above-mentioned object of the present invention is achieved through the following technical solutions:

[0009] The present invention first provides a method for preparing a copper zinc tin sulfur (CZTS) precursor film, comprising the following steps:

[0010] S1. According to the molar ratio: Cu / (Zn+Sn)=0.5-0.8, Zn / Sn=1.0-1.5, the total molar concentration of Cu+Sn+Zn is 0.5-5 mol / L, and the thiourea / total metal ion concentration ratio is 1-3, copper salt, zinc salt, tin salt, and thiourea are weighed, and ethylene glycol methyl ether is used as a solvent, and dissolved and stirred to obtain a clear and transparent solution, and filtered to obtain an ink solution;

[0011] S2. The ink solution obtained in step S1 is inkjet printed on the substrate at a printing resolution of 250-300×250-300 dpi, and heat treated at 250-350° C. for 2-4 min. The inkjet printing and heat treatment are repeated until a copper-zinc-tin-sulfur precursor film with a thickness of 1-2 μm is obtained.

[0012] The present invention changes the traditional solution ink system and uses ethylene glycol monomethyl ether (MOE) as a solvent to prepare an air-stable ink system, which can be used for inkjet printing to prepare CZTS precursor films, and further prepare CZTSSe films and solar cells thereof. Using MOE as a solvent greatly improves the chemical stability of the precursor ink solution, and it remains clear and transparent after long-term placement, is not easy to produce precipitation, avoids clogging the printer nozzle, and realizes the long-term stability of the multi-component complex system of the precursor solution, which is suitable for long-term industrial production; and optimizes the parameters of inkjet printing, based on a printing resolution of 250-300×250-300dpi combined with MOE system ink to obtain high-quality CZTS and CZTSSe films, and then obtains a high-efficiency CZTSSe thin film solar cell.

[0013] Furthermore, in step S1, copper salt, zinc salt, tin salt and thiourea are weighed according to the molar ratios of Cu / (Zn+Sn)=0.7, Zn / Sn=1.05, the total molar concentration of Cu+Sn+Zn is 1.8 mol / L, and the concentration of thiourea is 3.2 mol / L.

[0014] Furthermore, the copper salt in step S1 is one of cuprous chloride, cupric chloride, cupric bromide, and cupric oxide; the zinc salt is one of anhydrous zinc acetate, zinc acetate dihydrate, zinc chloride, and zinc bromide; and the tin salt is one of anhydrous tin tetrachloride, crystalline water tin tetrachloride, tin acetate, and tin dichloride.

[0015] Preferably, the copper salt is cuprous chloride, the zinc salt is anhydrous zinc acetate, and the tin salt is anhydrous tin tetrachloride.

[0016] Furthermore, the stirring in step S1 is heating stirring at 50-60°C.

[0017] Preferably, the stirring in step S1 is heating stirring at 55°C.

[0018] Furthermore, the filtration in step S1 is performed by using a 750-850 nm filter membrane; preferably, polytetrafluoroethylene (PTFE) is used for filtration.

[0019] Preferably, the filtration in step S1 is performed by filtering with an 800 nm filter membrane.

[0020] Furthermore, the substrate in step S2 includes but is not limited to molybdenum glass, ITO or FTO.

[0021] Preferably, the substrate is molybdenum glass.

[0022] Furthermore, in step S2, the substrate is firstly ultrasonically cleaned with acetone, ethanol and deionized water respectively, blown dry with a nitrogen air gun, and then plasma cleaned.

[0023] Preferably, the cleaning power of the plasma cleaning is 4 to 6 W, and the cleaning time is 2 to 8 minutes.

[0024] The present invention provides a copper-zinc-tin-sulfur precursor film prepared by any of the above-mentioned preparation methods.

[0025] The present invention provides application of the copper-zinc-tin-sulfur precursor film in preparing a copper-zinc-tin-sulfur-selenium film.

[0026] The present invention also provides a method for preparing a copper zinc tin sulfur selenium (CZTSSe) film. The method comprises distributing 300 to 600 mg of Se in the copper zinc tin sulfur precursor film and performing selenization annealing to form the CZTSSe film.

[0027] Furthermore, the selenization annealing conditions are: firstly raising the temperature to 500-550° C., maintaining it for 10-25 minutes in a nitrogen atmosphere at normal pressure, and finally naturally cooling it to room temperature.

[0028] Preferably, the selenization annealing conditions are: firstly raising the temperature to 535° C., maintaining it for 15 minutes in a nitrogen atmosphere at normal pressure, and finally naturally cooling it to room temperature.

[0029] The present invention also provides a copper-zinc-tin-sulfur-selenium thin film prepared by any of the above-mentioned preparation methods.

[0030] The present invention provides the use of the copper-zinc-tin-sulfur precursor film or the copper-zinc-tin-sulfur-selenium film in preparing a thin-film solar cell.

[0031] Furthermore, the thin film solar cell is a copper-zinc-tin-sulfur-selenium thin film solar cell.

[0032] The present invention also provides a method for preparing a copper zinc tin sulfur selenium thin film (CZTSSe) solar cell, which comprises: depositing a cadmium sulfide (CdS) buffer layer on the copper zinc tin sulfur selenium thin film obtained above by a chemical bath deposition (CBD) method; subsequently sputtering i-ZnO and ITO as a window layer by a magnetron sputtering method; and then evaporating an Ag electrode by a thermal evaporation method to complete the preparation of the CZTSSe thin film solar cell.

[0033] Furthermore, the method specifically comprises depositing a 50 nm thick cadmium sulfide (CdS) buffer layer on the copper-zinc-tin-sulfur-selenide thin film by chemical bath deposition (CBD); subsequently, sputtering 50 nm of i-ZnO and 150 nm of ITO as a window layer by magnetron sputtering; and then thermally evaporating a 300 nm thick Ag electrode to complete the preparation of a CZTSSe thin film solar cell.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] The present invention first provides a method for preparing a copper-zinc-tin-sulfur film, by changing the traditional solution ink system, using ethylene glycol methyl ether as a solvent to prepare an air-stable ink system, after being placed in an atmospheric environment for 30 days, the ink solution still presents a clear and transparent state; using ethylene glycol methyl ether as a solvent greatly improves the chemical stability of the precursor ink solution, and it remains clear and transparent after long-term placement, is not easy to produce precipitation, avoids clogging the printer nozzle, and realizes the long-term stability of the precursor solution multi-component complex system, which is suitable for long-term industrial production; at the same time, based on the printing resolution of 250-300×250-300dpi, a CZTS precursor film is obtained in combination with ethylene glycol methyl ether system ink, and further high-quality CZTSSe film and thin-film solar cell thereof can be prepared. The present invention adopts inkjet printing technology to prepare CZTSSe film, which has the advantages of low loss and low cost, and can prepare high-performance and high-efficiency CZTSSe thin-film solar cells. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the precursor solution initially prepared in Example 1.

[0037] Figure 2 This is the precursor solution of Example 1 after being left for 30 days.

[0038] Figure 3 SEM surface morphologies of CZTSSe films obtained at different printing resolutions; a is 250×250dpi, b is 300×300dpi, and c is 350×350dpi.

[0039] Figure 4 The performance statistics of the device assembled with CZTSSe thin films obtained at different printing resolutions, where a is the Voc open circuit voltage result, b is the JSC short circuit current density result, c is the fill factor (FF) result, and d is the battery conversion efficiency result.

[0040] Figure 5 The surface morphology of the CZTSSe film obtained at a printing resolution of 300×300 dpi (left) and the JV image of the assembled device (right). DETAILED DESCRIPTION

[0041] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0042] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0043] Example 1

[0044] The precursor solution is prepared with compound reagents such as copper, zinc, and tin, wherein the solvent is ethylene glycol methyl ether (MOE). Preparation of the precursor ink solution: cuprous chloride, anhydrous zinc acetate, anhydrous tin tetrachloride, and thiourea dissolved in MOE are mixed in sequence, wherein the optimal value is: the molar ratio Cu / (Zn+Sn) is 0.7, Zn / Sn=1.05, and the total molar concentration of Cu+Sn+Zn is 1.8 mol / L. The thiourea concentration is 3.2 mol / L. The solution is then stirred at 400-600 rpm at 55°C until a clear and transparent ink solution is obtained, and finally filtered with 800nm ​​PTFE to obtain an MOE-based ink solution.

[0045] The stability of the MOE-based ink solution was observed after long-term storage: the initially prepared ink solution was clear and transparent. Figure 1 After 30 days in the atmosphere, the MOE-based ink solution still appears clear and transparent. Figure 2 Therefore, the ink based on the MOE system has good stability.

[0046] Example 2

[0047] The precursor solution is prepared with compound reagents such as copper, zinc, and tin, wherein the solvent is ethylene glycol methyl ether (MOE). Preparation of the precursor ink solution: cuprous chloride, anhydrous zinc acetate, anhydrous tin tetrachloride, and thiourea dissolved in MOE are mixed in sequence, wherein the optimal value is: the molar ratio Cu / (Zn+Sn) is 0.5, Zn / Sn=1.0, and the total molar concentration of Cu+Sn+Zn is 0.5 mol / L. The concentration of thiourea is 0.5 mol / L. The solution is then stirred at 400-600 rpm at 50°C until a clear and transparent ink solution is obtained, and finally filtered with 800nm ​​PTFE to obtain an MOE-based ink solution.

[0048] The MOE-based ink solution remains clear and transparent after being placed for a long time.

[0049] Example 3

[0050] The precursor solution is prepared with compound reagents such as copper, zinc, and tin, wherein the solvent is ethylene glycol methyl ether (MOE). Preparation of the precursor ink solution: cuprous chloride, anhydrous zinc acetate, anhydrous tin tetrachloride, and thiourea dissolved in MOE are mixed in sequence, wherein the molar ratio is: Cu / (Zn+Sn) at 0.8, Zn / Sn=1.5, and the total molar concentration of Cu+Sn+Zn is 5 mol / L. The concentration of thiourea is 15 mol / L. The solution is then stirred at 400-600 rpm at 60°C until a clear and transparent ink solution is obtained, and finally filtered with 800nm ​​PTFE to obtain an MOE-based ink solution.

[0051] The MOE-based ink solution remains clear and transparent after being placed for a long time.

[0052] Example 4

[0053] A precursor ink solution is prepared using copper, zinc, tin and other compound reagents, wherein the solvent is ethylene glycol methyl ether (MOE), and the copper zinc tin sulfur selenium (CZTSSe) thin film and its solar cell are prepared by inkjet printing technology using the precursor solution ink. The specific steps are as follows:

[0054] Step 1: Preparation of precursor solution: The ink solution used in this example is synthesized in Example 1.

[0055] Step 2: Preparation of copper zinc tin sulfur (CZTS) thin film: Place the ink solution prepared in step 1 into the inkjet printing ink cartridge, set the printing parameters and run the inkjet printer to print the ink on the molybdenum glass substrate. After each printing, place it on a hot plate and heat treat it at 280°C for 2 minutes. Repeat the printing and heat treatment process multiple times to obtain a CZTS precursor film with a thickness of 1 to 2 μm; the printing parameters and printing resolutions are set to 250×250dpi, 300×300dpi, and 350×350dpi, respectively.

[0056] Step 3: Preparation of copper zinc tin sulfur selenium (CZTSSe) film: This step is to place the CZTS film obtained in step 2 in a graphite box, and evenly distribute 500 mg of Se particles around the CZTS film, and then place them together in a rapid thermal processing furnace for selenization annealing to form a CZTSSe film. The specific selenization conditions in the annealing furnace are: first increase the temperature from room temperature to 535°C within 60 seconds, then maintain it in a nitrogen atmosphere at normal pressure for 900 seconds, and finally take out the selenized sample after naturally cooling to room temperature.

[0057] Step 4: Device preparation: A cadmium sulfide (CdS) buffer layer of about 50 nm is deposited on the CZTSSe film obtained after selenization by chemical bath deposition (CBD); then a 50 nm i-ZnO and a 150 nm ITO window layer are sputtered by magnetron sputtering; and then a 300 nm Ag electrode is evaporated by thermal evaporation to complete the preparation of the entire CZTSSe thin film solar cell.

[0058] Device performance measurement: The surface morphology of CZTSSe films at different printing resolutions was observed. Figure 3 As shown, the film obtained at 300×300 dpi printing resolution is smoother and denser. Figure 4 The following is a statistical comparison of the optoelectronic performance of CZTSSe thin films assembled into devices obtained at different printing resolutions. Among them, the effect of 350×350dpi printing resolution is poor, and the photoelectric conversion efficiency is less than 10%, while the devices assembled from CZTSSe thin films obtained at 250×250dpi and 300×300dpi printing resolutions have good optoelectronic performance. High-quality CZTSSe thin films were prepared by inkjet printing at 300×300dpi printing resolution ( Figure 5 left), and also exhibited the highest photoelectric conversion efficiency ( Figure 5 Right picture), indicating that the use of ink of MOE system for inkjet printing to prepare CZTSSe thin film is beneficial to obtain high-performance photovoltaic devices. The ink system prepared in Examples 2 and 3, the photovoltaic device further assembled by inkjet printing of CZTSSe thin film also has high performance. In summary, the CZTSSe thin film is prepared by inkjet printing at a printing resolution of 250-300dpi×250-300dpi using the precursor solution ink based on the MOE system, and the CZTSSe solar cell prepared thereby has good device performance, among which the device obtained at a printing resolution of 300×300dpi has the best performance and the highest photoelectric conversion efficiency of 12.86%, which is the highest performance of CZTSSe thin film solar cells currently obtained based on inkjet printing technology.

[0059] Example 5

[0060] The method is basically the same as Example 4, except that in step 3: 300 mg of Se particles are evenly distributed around the CZTS film during the preparation of the CZTSSe film. The prepared CZTSSe thin film solar cell also has a high photoelectric conversion efficiency.

[0061] Example 6

[0062] The method is basically the same as Example 4, except that in step 3: 600 mg of Se particles are evenly distributed around the CZTS film during the preparation of the CZTSSe film. The prepared CZTSSe thin film solar cell also has a high photoelectric conversion efficiency.

[0063] Comparative Example

[0064] The device assembled from the CZTSSe thin film obtained by inkjet printing with the precursor solution ink based on the DMSO system is used for comparison. Since different systems have different suitable conditions for inkjet printing, such as the metal concentration in the precursor solution ink and the printing parameters, the metal concentration in the precursor solution ink prepared based on the DMSO system and the printing resolution of inkjet printing are first optimized. The optimal printing resolution is 250×250dpi. The highest performance parameters of the device prepared by inkjet printing based on the DMSO system are obtained by testing, and then compared with the device performance obtained at a printing resolution of 300×300dpi in Example 4.

[0065] The comparison results are shown in Table 1. The maximum conversion efficiency of the CZTSSe thin film solar cell prepared by the present invention is nearly 40% higher than that of the CZTSSe thin film solar cell based on the DMSO system. At the same time, the CZTSSe thin film solar cell prepared by the present invention is also higher than the CZTSSe thin film solar cell prepared by inkjet printing using DMSO system ink in the prior art (Ge Sijie.Cu 2 ZnSn(S,Se) 4 Study on the regulation of printable inks and performance of photovoltaic devices [D]. Sun Yat-sen University, 2022) The highest cell conversion efficiency obtained. Table 1 Performance comparison of the highest performance device based on the DMSO system and the highest performance device based on the MOE system

[0066]

Claims

1. A method for preparing a copper-zinc-tin-sulfur precursor film, characterized in that: The following steps are involved: S1. According to the molar ratio: Cu / (Zn+Sn)=0.5-0.8, Zn / Sn=1.0-1.5, the total molar concentration of Cu+Sn+Zn is 0.5-5 mol / L, and the total molar concentration ratio of thiourea / Cu+Sn+Zn is 1-3, copper salt, zinc salt, tin salt, thiourea are weighed, ethylene glycol methyl ether is used as a solvent, dissolved and stirred to obtain a clear and transparent solution, and filtered to obtain an ink solution; S2. The ink solution obtained in step S1 is inkjet printed on the substrate at a printing resolution of 250-300×250-300 dpi, and heat treated at 250-350° C. for 2-4 min. The inkjet printing and heat treatment are repeated until a copper-zinc-tin-sulfur precursor film with a thickness of 1-2 μm is obtained.

2. The preparation method according to claim 1, characterized in that: The copper salt in step S1 is one of cuprous chloride, cupric chloride, cupric bromide, and cupric oxide; the zinc salt is one of anhydrous zinc acetate, zinc acetate dihydrate, zinc chloride, and zinc bromide; and the tin salt is one of anhydrous tin tetrachloride, crystal water tin tetrachloride, tin acetate, and tin dichloride.

3. The preparation method according to claim 1, characterized in that: Before plasma cleaning, the molybdenum glass in step S2 is first ultrasonically cleaned with acetone, ethanol, and deionized water, blown dry with a nitrogen air gun, and then plasma cleaned.

4. The preparation method according to claim 3, characterized in that: The cleaning power of the plasma cleaning is 4 to 6 W, and the cleaning time is 2 to 8 minutes.

5. The copper-zinc-tin-sulfur precursor film prepared by the preparation method according to any one of claims 1 to 4.

6. Use of the copper-zinc-tin-sulfur precursor film according to claim 5 in the preparation of a copper-zinc-tin-sulfur-selenium film.

7. A method for preparing a copper-zinc-tin-sulfur-selenium thin film, characterized in that: 300-600 mg of Se is distributed around the copper-zinc-tin-sulfur precursor film of claim 5, and selenization annealing is performed to form a CZTSSe film.

8. The preparation method according to claim 7, characterized in that: The selenization annealing conditions are: firstly raising the temperature to 500-550° C., maintaining it for 10-25 minutes in a nitrogen atmosphere at normal pressure, and finally cooling it to room temperature.

9. The copper-zinc-tin-sulfur-selenium thin film prepared by the preparation method according to claim 7 or 8.

10. Use of the copper-zinc-tin-sulfur precursor film according to claim 5 or the copper-zinc-tin-sulfur-selenium film according to claim 9 in the preparation of thin-film solar cells.

Citation Information

Patent Citations

  • Method of regulating back crystallization of copper-zinc-tin-sulfur (selenium) solar cell absorption layer

    CN110459626A

  • Preparation methods of modified copper-zinc-tin-sulfur precursor solution and thin film solar cell

    CN114899279A

  • Copper-zinc-tin-sulfur-selenium thin film, preparation method and copper-zinc-tin-sulfur-selenium thin film solar cell comprising same

    CN117133660A

  • Copper-zinc-tin-sulfur precursor solution and preparation method and application thereof

    CN117457761A